Wind and trophic status explain within and among‐lake variability of algal biomass. Issue 6 (30th October 2018) - Rusak, J. A.; Tanentzap, A. J.; Klug, J. L.; Rose, K. C.; Hendricks, S. P.; Jennings, E.; Laas, A.; Pierson, D.; Ryder, E.; Smyth, R. L.; White, D. S.; Winslow, L. A.; et al.
Abstract: Phytoplankton biomass and production regulates key aspects of freshwater ecosystems yet its variability and subsequent predictability is poorly understood. We estimated within‐lake variation in biomass using high‐frequency chlorophyll fluorescence data from 18 globally distributed lakes. We tested how variation in fluorescence at monthly, daily, and hourly scales was related to high‐frequency variability of wind, water temperature, and radiation within lakes as well as productivity and physical attributes among lakes. Within lakes, monthly variation dominated, but combined daily and hourly variation were equivalent to that expressed monthly. Among lakes, biomass variability increased with trophic status while, within‐lake biomass variation increased with increasing variability in wind speed. Our results highlight the benefits of high‐frequency chlorophyll monitoring and suggest that predicted changes associated with climate, as well as ongoing cultural eutrophication, are likely to substantially increase the temporal variability of algal biomass and thus the predictability of the services it provides.